2011
DOI: 10.1016/j.semcdb.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynaptic and nonvesicular ATP release from neurons and relevance to neuron–glia signaling

Abstract: Studies on the release of ATP from neurons began with the earliest investigations of quantal neurotransmitter release in the 1950s, but in contrast to ATP release from other cells, studies of ATP release from neurons have been narrowly constrained to one mechanism, vesicular release. This is a consequence of the prominence of synaptic transmission in neuronal communication, but nonvesicular mechanisms for ATP release from neurons are likely to have a broader range of functions than synaptic release. Investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 102 publications
1
73
0
Order By: Relevance
“…Here, we showed that stimulation of L1 signaling also triggers tyrosine phosphorylation of ANT1, ANT2, and MMP14 and reduces intracellular ATP levels, being associated with transient ANT-dependent release of ATP (Fig. 10 B), which could act as a neurotransmitter or extracellularly phosphorylate neuritogenic molecules (Fields, 2011;Lalo et al, 2011) (Fig. 10 B).…”
Section: L1-mediated Signaling Events Underlying Neuritogenesis Involmentioning
confidence: 88%
“…Here, we showed that stimulation of L1 signaling also triggers tyrosine phosphorylation of ANT1, ANT2, and MMP14 and reduces intracellular ATP levels, being associated with transient ANT-dependent release of ATP (Fig. 10 B), which could act as a neurotransmitter or extracellularly phosphorylate neuritogenic molecules (Fields, 2011;Lalo et al, 2011) (Fig. 10 B).…”
Section: L1-mediated Signaling Events Underlying Neuritogenesis Involmentioning
confidence: 88%
“…The mechanism of nucleotide release from cells is currently not sufficiently understood. Recently, several mechanisms for ATP release from cells have been proposed, and they are activated by a wide range of stimuli (52,53). These ATP release mechanisms include damage to the cell membrane, mechanical stress, hypoxia, inflammation, several agonists, and electrical excitation of neural tissue.…”
Section: Discussionmentioning
confidence: 99%
“…67 Astrocytes and oligodendrocytes express all 4 subtypes of P1 receptors and their activation induces Ca 2+ release from internal stores in both cell types, and regulates oligodendrocyte maturation and myelination. 68 Moreover, central axonal conduction may be modulated by adenosine because blockade of A1 receptors in axon shafts also increases the width of action potentials. 60 ATP signaling in WM astrocytes and oligodendrocytes occurs through a variety of P2X receptors, which are highly Ca 2+ permeable, and P2Y receptors, which mobilize Ca 2+ from intracellular stores.…”
Section: Wm Signaling By Neurotransmittersmentioning
confidence: 99%
“…12,77 Thus, oligodendrocytes can be partially protected from irreversible ischemic injury, including perinatal ischemia, by glutamate receptor antagonists and glutamate uptake inhibitors 11,[16][17][18][19][20] (Table; Figure 3; refs. 44,68). In models of developing WM, simulated ischemia induces an inward current in oligodendrocytes that is mediated, in part, by NMDA and AMPA/kainate receptors, 19 and increases Ca 2+ levels in myelin itself (an effect Figure 3.…”
Section: +mentioning
confidence: 99%